Period of Efficient Underwater Hull Cleaning - Wijaya, Rifqi Al Baihaqi; Baidowi, Achmad; Sunarsih (International Journal of Marine Engineering Innovation and Research, 2025)
Biofouling is a collection of unwanted living organisms on surfaces submerged in water. Biofouling is a complex occurrence caused by various physical and environmental factors that can be overcome by regular hull cleaning. The main purpose of underwater hull cleaning is to remove dirt and restore propulsion efficiency. Another benefit of hull cleaning against biofouling is to restore or rejuvenate the effectiveness of antifouling paint. This study aims to determine the extent of the effect of periodic hull cleaning on the underwater area, where the results can be used to determine the most efficient period for periodic hull cleaning and the percentage of fuel that can be saved by performing periodic underwater cleaning.The effect of biofouling can be predicted by conducting simulations using Computational Fluid Dynamics (CFD) with several variations in hull roughness. The results of the CFD simulation show that the increase in resistance with the largest surge occurs in the 18th period with an average increase of 5.8%. Therefore, the effective time to perform underwater hull cleaning is in the 18th period. Performing underwater hull cleaning in the 18th period can save fuel consumption by up to 5.8%.